The Role of Phase Hardness Differential on the Non-uniform Elongation of a Ferrite-Martensite Dual Phase Steel - Soudip Basu; Jaya, Balila Nagamani; Anirban Patra; Sarbari Ganguly; Monojit Dutta; Anton Hohenwarter; Indradev Samajdar (Metallurgical and Materials Transactions A: Physical Metallurgy and Materials Science, 2021)
This study involved a commercial hot-rolled dual-phase (DP) steel consisting of martensite ( 10 pct) and ferrite phases. The harder lath martensite was located at the grain boundaries and triple junctions of the equiaxed ferrite grains. Tempering and high-pressure torsion (HPT) were used to alter the phase hardness differential ∆H (where ΔH=HMartensite−HFerrite) of the DP. The relationship between ∆H and non-uniform elongation, εNU, or post-necking ductility under tensile deformation, was then explored. Tempering softened predominantly the martensite, while HPT increased the ferrite hardness. Both led to a reduction in ∆H. A drop in ∆H in the tempered DP resulted in a steady increase and eventual saturation in εNU. On the other hand, a ∆H decrease in the HPT specimens showed an initial increase in εNU followed by a drop. Strain analysis, with optical digital image correlation during tensile deformation of the tempered DP samples, clearly related the formation of strain localization with ∆H. In particular, severity of strain localization during necking scaled linearly with ∆H. This study thus brought out a potential relationship among the phase hardness differential (∆H), severity of strain localizations and post-necking ductility (εNU).
Publisher Copyright: extcopyright 2021, The Minerals, Metals & Materials Society and ASM International.